Comparison of Various Sky Model for Daylighting Availability Inside The Classroom with Bilateral Opening Typology in The Tropics - Atthaillah, Atthaillah; Iqbal, Muhammad; Badriana, Badriana; Nabila, Putri Sri Alisia (Journal of Applied Engineering and Technological Science (JAETS), 2025)
This study compares daylighting performance under four sky models of a classroom in tropical climates to understand the differences in illuminance and uniformity values. This research is significant as it can inform the relevance of the widely used static metric, such as the daylight factor, for daylight performance evaluation in tropical climates in comparison with the climate-based sky model which is utilized for dynamic metric calculation. Computational simulation was employed to achieve the objective. Grasshopper-Rhinoceros was utilized for the classroom model, while Radiance was employed for sky modelling and daylight simulation. The results indicated that static sky models exhibited greater discrepancies in their average illuminance and uniformity values compared to climate-based or dynamic sky models. The pervasive utilization of static metrics, such as the daylight factor, for evaluating daylighting performance within a space may necessitate reconsideration in tropical climates, given the higher error rates observed in this study for a classroom with bilateral opening design.